Analisis Pengaruh Rasio Profitabilitas, Rasio Aktivitas Dan Rasio Leverage Terhadap Opini Audit Going Concern Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Dinul Qayyim; Fitriyah, Nur (Jurnal Riset Mahasiswa Akuntansi, 2025)
This research aims to analyze the influence of profitability ratios, activity ratios and leverage ratios on going concern audit opinions on companies listed on the Indonesia Stock Exchange (BEI). Going concern is an important aspect of an audit that reflects the company's ability to maintain its business continuity. Auditors consider various financial factors before providing a going concern audit opinion, including the company's profitability, activity and leverage. The research method used is quantitative analysis with secondary data obtained from the financial reports of coal mining sector companies listed on the IDX for the 2020-2023 period. Data analysis was carried out using descriptive statistical tests to test the influence of independent variables on going concern audit opinion. The research results show that profitability ratios as measured by GPM, NPM, ROA and ROE have a negative effect on the acceptance of going concern audit opinions. The activity ratio as measured by ITO, ART, ATO has a negative influence on going concern audit opinion, which means that the higher the company's effectiveness in managing its assets, the smaller the possibility of getting a going concern audit opinion. Meanwhile, the leverage ratio as measured by DER, DAR has a significant influence on going concern audit opinions, indicating that companies with a high level of leverage are more at risk of getting this opinion.